Diagnóstico de la enfermedad del tracto urinario inferior en pacientes felinos atendidos en una clínica veterinaria de la ciudad de Loja - Peña Cruz, Andrea Carolina (2023)
Feline lower urinary tract disease (FLUTD); comprises a series of pathologies that can affect the bladder and/or urethra of cats, taking into consideration urolithiasis, idiopathic cystitis and urethral plugs, among others presenting through several similar clinical signs, such as hematuria, dysuria, strangury, frequency and spontaneous urination, mostly idiopathic. The purpose of this work was to diagnose Lower Urinary Tract Disease of feline patients in a veterinary clinic in the city of Loja during the period October-November 2022. A population of 53 feline patients was studied obtaining a total of 6 felines; positive for FLUTD; taking into account the frequency of the disease, considering possible factors associated with the variables: race, age, sex, diet and reproductive status. In addition to the causal pathologies. For the statistical analysis of the data, the Chi Square test of goodness was used, considering p values less than or equal to 0.05 as statistically significant. It was determined that none of the variables was significant according to the p value in the presence of the exposed pathology. Finally, the results obtained indicate that urolithiasis turned out to be the most frequent pathology in the presence of FLUTD, with 66.66%. Keywords: FLUTD, feline, Cystitis, Urolithiasis, Obstruction.